Part of the one Church?: the ordination of women and Anglican identity - Greenacre, Roger (Canterbury Press, 2014)
Part of One Church offers a classical understanding of the Church of England's identity and its place as part of the 'One, Holy, Catholic and Apostolic Church'. Though not opposed in principle to women's ordination to the priesthood, Roger Greenacre articulates with creative courtesy the ecclesiological reasons why so many cannot accept its implementation in the Church of England when it lacks the consent of the wider Church. In doing so he addresses issues that remain topical and significant. Roger's frame of reference is wide: his thinking and writing are deeply enriched by the Anglican tradition and his hope is that its distinctive heritage might be brought into communion with the Catholic Church